Performance of Seven Peach Rootstocks in a Brazilian Subtropical Climate - Oliveira, João Alison Alves; Bruckner, Cláudio Horst; Gomes, Francielly Rodrigues [UNESP]; da Assunção, Hildeu Ferreira; Cruz, Simério Carlos Silva; da Silva, Danielle Fabíola Pereira (Friends Science Publishers, 2022)
The commercial orchards of peach trees are propagated by grafting, and the combination of rootstock and scion cultivars has significant importance to produce quality fruits. Many studies evaluating the influence of scion cultivars on fruit yield and quality have been executed, but studies on rootstocks under subtropical climate conditions in Brazil are still incipient, making it necessary to evaluate the performance of new rootstocks. This study aimed to evaluate the performance of seven rootstocks based on tree growth, fruit quality, and yield of the scion cultivars Aurora 1 and Tropic Beauty in Brazilian subtropical climate conditions. Seven rootstocks were evaluated from the UFV breeding program (UFV 1701-2, UFV 102-1, UFV 186, UFV 1701-1, UFV 102-2, UFV 286 and UFV 202-1) and one control representing the cultivar most used in the southeastern Brazil (Okinawa). A randomized block design was arranged, with sixteen treatments and five replications. The variables evaluated were trunk cross-sectional area, plant height, fresh weight of pruned material, production per plant, yield, fruit weight, fruit size, skin color, firmness, and soluble solids content. The cultivars Aurora 1 and Tropic Beauty presented a less vigorous growth when grafted onto the rootstocks UFV 186, UFV 286 and UFV 102-1, being suitable for high-density plantings, and a greater yield when grafted onto UFV 1701-1, UFV 1701-2 and UFV 202-1. The fruit weight was similar for all the rootstocks tested, and the quality of fruits from Aurora 1 and Tropic Beauty did not differentiate from the control Okinawa, which means that the performance of the rootstocks from the UFV breeding program meets the standards required by the market and their use can be successful in regions of subtropical climate.
Keywords: Aurora 1; Fruit quality; Productivity; Prunus persica (l.) batsch; Tropic beauty; Vigor